An Approach to Evaluate the Clothing Creative Design with Dual Hesitant Fuzzy Information - Ya-Mei Li (Journal of Control Science and Engineering)
The problem of evaluating the clothing creative design with dual hesitant fuzzy information is the multiple attribute decision making problem. In this paper, we have utilized dual hesitant fuzzy hybrid average (DHFHA) operator to develop the model to solve the multiple attribute decision making problems for evaluating the clothing creative design. Finally, a practical example for evaluating the clothing creative design is given to verify the developed approach.